Polyelectrolyte carbon-based hydrogel as well as preparation method and application thereof

Through polyelectrolyte regulation directional frozen casting technology, polyelectrolyte carbon-based hydrogel with adjustable pore structure was prepared, which solved the problem of difficult control of the pore structure of existing carbon-based photothermal hydrogel materials, and improved the high-salt environment Solar desalination efficiency.

CN119307058AActive Publication Date: 2025-01-14JIANGXI SCI & TECH NORMAL UNIV

Patent Information

Application Number
CN202411419245.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The pore structure of existing carbon-based photothermal hydrogel materials is difficult to regulate, resulting in low efficiency of solar seawater desalination in high-salt environments.

Method used

Polyelectrolytes are used to regulate the nucleation size of ice during directional frozen casting to prepare polyelectrolyte carbon-based hydrogels with adjustable pore structures. The nucleation of ice crystals is regulated through the electrostatic action of polyelectrolyte and water molecules to form an orderly oriented three-dimensional porous network structure.

Benefits of technology

The controllable structure of small-size oriented pores is realized, the water evaporation rate and porosity are improved, the photothermal conversion capability is enhanced in high-salt environments, and it is suitable for efficient solar seawater desalination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307058A_ABST
    Figure CN119307058A_ABST
Patent Text Reader

Abstract

The invention discloses polyelectrolyte carbon-based hydrogel as well as a preparation method and application thereof. The polyelectrolyte carbon-based hydrogel has an ordered orientation three-dimensional porous network structure formed by crosslinking of water-soluble gel, polyelectrolyte and nanocarbon. The preparation method comprises the following steps: uniformly mixing water-soluble gel, water and a nano carbon material to obtain a first mixed solution; uniformly mixing polyelectrolyte with the first mixed solution to obtain a second mixed solution, and adjusting the pH value; mixing the second mixed solution and a cross-linking agent, and performing directional freezing casting to obtain frozen nano composite gel; and performing freeze drying on the frozen nano carbon composite gel to obtain polyelectrolyte carbon-based aerogel, and soaking the polyelectrolyte carbon-based aerogel in water to obtain the polyelectrolyte carbon-based hydrogel. The porous structure of the hydrogel is effectively regulated and controlled in the directional freezing casting process through the polyelectrolyte, and the polyelectrolyte carbon-based hydrogel has a small-pore hierarchical pore structure, has high photo-thermal conversion and light absorption capacity and can be applied to the field of photo-thermal water evaporation purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation, and specifically relates to a polyelectrolyte carbon-based hydrogel and a preparation method and application thereof. Background Art

[0002] Solar water evaporation system has low cost and high energy efficiency, which is of great significance to alleviate energy crisis, reduce water pollution and promote seawater desalination. According to the types of photothermal materials, they are divided into: metal materials, semiconductor materials, carbon-based materials and polymer materials. Carbon-based photothermal materials have wide spectrum absorption characteristics, and the water evaporation energy of photothermal water gel is adjustable. Therefore, carbon-based photothermal water gel has become a key material for the development of solar photothermal seawater desalination technology.

[0003] In the study of hydrogel photothermal materials, the focus needs to be on the effect of its water transport performance on photothermal water evaporation. Efficient water transport channels not only provide sufficient water supply for rapid water evaporation, but also realize the controllable construction of salt-resistant surfaces, which is helpful for the development of highly salt-resistant solar desalination structures. At present, carbon-based photothermal water gel materials have developed composite structures of nano-carbon dispersed particles and polymer hydrogels, and photothermal water gels composited with continuous nano-carbon networks and polymers. Both carbon-based hydrogel structures have rich pore structures. Carbon-based hydrogels with composite structures of nano-carbon dispersed particles and polymer hydrogels, such as the carbon-based hydrogels involved in CN118047973A, use freeze casting to construct a multi-level ordered pore structure, but due to their large pore size, the capillary action of the water transport process is small, so the water transport rate is low. The photothermal water gel of polymer composite continuous nano carbon network, such as the carbon nanotube hydrogel involved in CN1 12934129A, uses multi-level pore CNT aerogel and polymer hydrogel to obtain a carbon-based hydrogel with a double network structure. Its pore structure transports a disordered pore structure with multi-level distribution, and its water transport efficiency is low. Therefore, it is urgent to develop a controllable preparation method of nano carbon-based hydrogel with adjustable pore structure to achieve efficient solar desalination in a high-salt environment. Summary of the invention

[0004] The main purpose of the present invention is to provide a polyelectrolyte carbon-based hydrogel and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0005] To achieve the above-mentioned object of the invention, the technical solution of the present invention includes:

[0006] One aspect of the present invention provides a polyelectrolyte carbon-based hydrogel, wherein the polyelectrolyte carbon-based hydrogel has an ordered oriented three-dimensional porous network structure formed by cross-linking of a water-soluble gel, a polyelectrolyte, and nano-carbon.

[0007] Furthermore, the oriented pore size of the polyelectrolyte carbon-based hydrogel is 1 to 20 μm.

[0008] Another aspect of the present invention provides a method for preparing a polyelectrolyte carbon-based hydrogel, comprising:

[0009] Evenly mixing the water-soluble gel, water and the nano-carbon material to obtain a first mixed solution;

[0010] Mixing the polyelectrolyte and the first mixed solution uniformly to obtain a second mixed solution, and adjusting the pH value;

[0011] The second mixed solution and the cross-linking agent are mixed and subjected to directional freeze casting to obtain a frozen nanocomposite gel;

[0012] The frozen nano-carbon composite gel is freeze-dried to obtain a polyelectrolyte carbon-based aerogel, and then is soaked in water to obtain a polyelectrolyte carbon-based hydrogel.

[0013] Another aspect of the present invention provides a polyelectrolyte carbon-based hydrogel prepared by the aforementioned preparation method.

[0014] Another aspect of the present invention provides a polyelectrolyte carbon-based xerogel prepared by drying the aforementioned polyelectrolyte carbon-based hydrogel.

[0015] Another aspect of the present invention also provides the use of the aforementioned polyelectrolyte carbon-based hydrogel or polyelectrolyte carbon-based xerogel in the field of photothermal water evaporation purification.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects:

[0017] (1) The present invention regulates the size of ice nucleation during directional freeze casting by adding polyelectrolytes. Compared with the traditional freeze casting method for regulating pore morphology, the present invention has the advantage of adjustable pore shape and can realize the controllable construction of small-sized oriented pores. It is a universal method for preparing directional freeze cast carbon-based hydrogels.

[0018] (2) The polyelectrolyte carbon-based hydrogel prepared by the present invention has a strong light-to-heat conversion capability and a rich pore structure inside, and can be effectively applied to high-efficiency solar desalination in a high-salt environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1is a SEM image of a polyelectrolyte carbon-based hydrogel with efficient photothermal water evaporation in a high-salt environment in a typical embodiment of the present invention;

[0021] Figure 2 This is a physical picture of a polyelectrolyte carbon-based hydrogel for efficient photothermal water evaporation in a high-salt environment in a typical embodiment of the present invention;

[0022] Figure 3 is a stable infrared thermal image of a polyelectrolyte carbon-based hydrogel under a sunlight intensity in a typical embodiment of the present invention;

[0023] Figure 4 This is a stable infrared thermal image of a polyelectrolyte carbon-based xerogel under a sunlight intensity in a typical embodiment of the present invention. DETAILED DESCRIPTION

[0024] In view of the problem that the pore structure of carbon-based photothermal water gel materials is difficult to adjust and control in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice, which mainly adopts polyelectrolytes to regulate the nucleation size of ice in the directional freezing casting process to prepare a carbon-based hydrogel with an adjustable pore structure. The technical solution, its implementation process and principle will be further explained as follows, but it cannot be understood as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the content of the present invention still belong to the scope of protection of the present invention.

[0025] Polyelectrolytes are polymers with polar functional groups that have strong interactions with water molecules. They can regulate the growth structure of ice during freeze casting, thereby affecting the morphology of freeze casting pores. The present invention uses polyelectrolytes to regulate the nucleation size of ice during directional freeze casting, and develops a method for preparing polyelectrolyte carbon-based hydrogels. Compared with the traditional freeze casting method for regulating pore morphology, this strategy has the advantage of adjustable pore shape, and can achieve controllable construction of small-sized oriented pores. It is a universal method for preparing directional freeze casting carbon-based hydrogels, which can be used for the development of solar desalination technology in high-salt environments.

[0026] As one aspect of the technical solution of the present invention, a polyelectrolyte carbon-based hydrogel is provided, wherein the polyelectrolyte carbon-based hydrogel has an ordered oriented three-dimensional porous network structure formed by cross-linking of a water-soluble gel, a polyelectrolyte, and nano-carbon.

[0027] Furthermore, the oriented pore size of the polyelectrolyte carbon-based hydrogel is 1 to 20 μm.

[0028] Furthermore, the oriented pore size of the polyelectrolyte carbon-based hydrogel is 1 to 10 μm.

[0029] Furthermore, the porosity of the polyelectrolyte carbon-based hydrogel is 80-90%.

[0030] Furthermore, the polyelectrolyte carbon-based hydrogel is -2 Under the light power density, the water evaporation rate is 1.8~4.3kgm -2 h -1 .

[0031] As another aspect of the technical solution of the present invention, a method for preparing a polyelectrolyte carbon-based hydrogel is provided, comprising: uniformly mixing a water-soluble gel, water, and a nano-carbon material to obtain a first mixed solution;

[0032] Mixing the polyelectrolyte and the first mixed solution uniformly to obtain a second mixed solution, and adjusting the pH value;

[0033] The second mixed solution and the cross-linking agent are mixed and directionally frozen to obtain a frozen nanocomposite gel;

[0034] The frozen nano-carbon composite gel is freeze-dried to obtain a polyelectrolyte carbon-based aerogel, and then is soaked in water to obtain a polyelectrolyte carbon-based hydrogel.

[0035] In some embodiments, the preparation method specifically includes: mixing the water-soluble gel with water to obtain a polymer solution, adding nano-carbon material to obtain the first mixed solution.

[0036] In some preferred embodiments, the mass concentration of the water-soluble gel in the polymer solution is 10 to 50 mg / mL.

[0037] In some preferred embodiments, the mass concentration of the nanocarbon material in the first mixed solution is 0.1N2 mg / mL.

[0038] In some preferred embodiments, the water-soluble gel may include at least any one of chitosan, sodium alginate, polyvinyl alcohol, polyethylene glycol, etc., but is not limited thereto.

[0039] In some preferred embodiments, the nano-carbon material may include at least any one of graphene, carbon nanotubes, graphyne, fullerene, nano-carbon black, activated carbon, graphite powder, etc., but is not limited thereto.

[0040] In some embodiments, the preparation method specifically includes: stirring and mixing the polyelectrolyte and the first mixed solution to obtain a second mixed solution, adjusting the pH value to 1-2, stirring and then performing vacuum degassing treatment.

[0041] In some preferred embodiments, the polyelectrolyte may include at least any one of a polyanion electrolyte, a polycation electrolyte, a polyzwitterion electrolyte, etc., but is not limited thereto.

[0042] In some preferred embodiments, the polyanion electrolyte may include at least any one of polyacrylic acid, polyacrylamide, polymethacrylic acid, polystyrene sulfonic acid, polyvinyl phosphoric acid, etc., but is not limited thereto.

[0043] In some preferred embodiments, the polycation electrolyte may include at least any one of polyethyleneimine, polyethyleneamine, etc., but is not limited thereto.

[0044] In some preferred embodiments, the amphoteric polyelectrolyte may include at least any one of natural nucleic acid, protein, polydimethyldiallylammonium chloride-acrylamide-acrylic acid (P(DMDAAC-AM-AA)), etc., but is not limited thereto.

[0045] In some preferred embodiments, the mass concentration of the polyelectrolyte in the second mixed solution is 10N50 mg / mL.

[0046] In some preferred embodiments, the acid used to adjust the pH includes at least any one of hydrochloric acid, sulfuric acid, phosphoric acid, etc., but is not limited thereto.

[0047] In some preferred embodiments, the concentration of the acid is 0.1-1 mol / L.

[0048] In some preferred embodiments, the vacuum degassing treatment time is 20 to 60 minutes, the vacuum degree of the vacuum degassing treatment is 1 to 20 Pa, and the temperature of the vacuum degassing treatment is 15 to 30°C.

[0049] In some embodiments, the preparation method specifically comprises: adding the cross-linking agent dropwise into the second mixed solution, pouring the solution into a freeze casting mold, and obtaining a frozen nano-carbon composite gel by directional freeze casting.

[0050] In some preferred embodiments, the mass ratio of the cross-linking agent to the second mixed solution is 1:100 to 1:200.

[0051] In some preferred embodiments, the cross-linking agent comprises glutaraldehyde.

[0052] In some preferred embodiments, the temperature of the directional freeze casting is -20 to -196°C.

[0053] In some preferred embodiments, the directional freeze casting includes unidirectional freezing or bidirectional freezing.

[0054] In some preferred embodiments, the working environment of the directional freeze casting is a low-temperature constant temperature reaction bath or liquid nitrogen.

[0055] In some preferred embodiments, the raw material of the freeze casting mold may include at least any one of stainless steel, copper, aluminum, silicone, polytetrafluoroethylene, nylon, organic glass, etc., but is not limited thereto.

[0056] The present invention places the nanocarbon hydrogel in a freezing casting mold, and then performs unidirectional or bidirectional freezing of the freezing casting mold in a low-temperature constant-temperature reaction bath or liquid nitrogen. Compared with the traditional freezing method, ultra-fast freezing and controllable regulation of oriented pores can be achieved, which can reduce the phase separation phenomenon, thereby obtaining a more uniform gel network.

[0057] In some embodiments, the preparation method specifically includes: thawing the frozen nano-carbon composite gel at room temperature and letting it stand, freeze-drying it to obtain a polyelectrolyte carbon-based aerogel, and soaking it in water to obtain a polyelectrolyte carbon-based hydrogel.

[0058] In some preferred embodiments, the standing time is 1 to 3 hours.

[0059] In some preferred embodiments, the freeze-drying time is 24 to 72 hours, and the freeze-drying temperature is 10 to 30°C.

[0060] In some preferred embodiments, the vacuum degree of freeze-drying is 1N10 Pa.

[0061] In some preferred embodiments, the foaming time is 1 to 10 hours.

[0062] In some more specific embodiments, the preparation method specifically comprises:

[0063] The water-soluble gel is mixed with water to obtain a polymer solution with a mass concentration of 10 to 50 mg / mL of the water-soluble gel, and a nano-carbon material is added to obtain a first mixed solution with a mass concentration of 0.1 to 2 mg / mL of the nano-carbon material;

[0064] The polyelectrolyte and the first mixed solution are stirred and mixed uniformly to obtain a second mixed solution with a mass concentration of the polyelectrolyte of 10 to 50 mg / mL, and the pH value is adjusted to 1N2. After stirring uniformly, vacuum degassing treatment is performed in an environment of 1 to 20 Pa and a temperature of 15 to 30° C. for 20 to 60 minutes;

[0065] The cross-linking agent is added dropwise to the second mixed solution at a mass ratio of 1:100 to 1:200, poured into a freeze casting mold, and subjected to directional freeze casting at -20 to -196°C to obtain a frozen nano-carbon composite gel;

[0066] The frozen nano-carbon composite gel is thawed at room temperature for 1 to 3 hours, frozen in a refrigerator, and freeze-dried for 24 to 72 hours in an environment of vacuum degree 1 to 10 Pa and temperature 10 to 30° C. to obtain a polyelectrolyte carbon-based aerogel, and then soaked in water for 1 to 10 hours to obtain a polyelectrolyte carbon-based hydrogel.

[0067] As another aspect of the technical solution of the present invention, a polyelectrolyte carbon-based hydrogel prepared by the aforementioned preparation method is provided.

[0068] As another aspect of the technical solution of the present invention, a polyelectrolyte carbon-based xerogel prepared by drying the above-mentioned polyelectrolyte carbon-based hydrogel is also provided.

[0069] The polyelectrolyte carbon-based hydrogel prepared by the present invention uses the electrostatic interaction between polyelectrolytes and water molecules to regulate the nucleation size of frozen casting ice crystals, so as to realize the controllable preparation of polyelectrolyte carbon-based hydrogels with smaller pores. The oriented pore size of the polyelectrolyte carbon-based hydrogel can be adjusted in the range of 1 to 20 μm.

[0070] Moreover, the polyelectrolyte carbon-based hydrogel prepared by the present invention introduces molecular chains of different hydration functional groups through polymer network structure design, so that a richer hydration network is formed between the polymer chain and the water molecules through hydrogen bonding. In addition, the polyelectrolyte carbon-based hydrogel prepared by the present invention has significant photothermal properties, and the oriented pore structure helps to achieve controllable interfacial water transport, thereby achieving efficient interfacial photothermal water evaporation. Inside the polyelectrolyte carbon-based hydrogel, nanocarbon is loaded on the nanotube chain under the auxiliary action of the polymer water chain, so that the three-dimensional carbon nanotube has a larger specific surface area, so that there is abundant interfacial water inside.

[0071] As another aspect of the technical solution of the present invention, there is also provided the use of the aforementioned polyelectrolyte carbon-based hydrogel or polyelectrolyte carbon-based xerogel in the field of photothermal water evaporation purification.

[0072] Furthermore, the application includes application in seawater desalination, sewage treatment or heavy metal salt treatment, but is not limited thereto.

[0073] In summary, the polyelectrolyte carbon-based hydrogel prepared by the present invention has a strong light-to-heat conversion capability, has a rich pore structure inside, forms abundant interfacial water, and the polymer gel network and nanocarbon are cross-linked by non-covalent bonds to form a three-dimensional interpenetrating double network structure. These characteristics make the polyelectrolyte carbon-based hydrogel have excellent environmental stability in a high-salt environment, and have broad application prospects in the process of seawater desalination, sewage treatment, and heavy metal salt treatment.

[0074] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and several preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. For the test methods in the following embodiments that do not specify specific conditions, the test methods in the embodiments are all carried out under normal conditions. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0075] Example 1

[0076] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and liquid nitrogen freeze casting was used to obtain the frozen polyanionic CNT / PVA hydrogel. The frozen composite gel was thawed at room temperature and placed in pure water for 24 hours. The sample was frozen in a refrigerator and dried in a freeze dryer for 48 hours to obtain a polyanion-regulated CNT / PVA composite aerogel. The polyanion CNT / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The effect of the optical power density on the aerogel was also studied. -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 1.

[0077] Example 2

[0078] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polycationic polyethyleneimine (PEI) was dropped into the above mixed solution to form a mixed solution with a PEI concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the cross-linking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and liquid nitrogen freeze casting was used to obtain the frozen polycationic CNT / PVA hydrogel. The frozen composite gel was thawed at room temperature and placed in pure water for 24 h. The sample was frozen in a refrigerator and then dried in a freeze dryer for 48 h to obtain polycation-regulated CNT / PVA composite aerogel. The polycation-regulated CNT / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the hydrogel had a good optical power density of 1 kW m -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 1.

[0079] Example 3

[0080] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polydimethyldiallylammonium chloride-acrylamide-acrylic acid (P(DMDAAC-AM-AA)) of polyampholyte was dropped into the above mixed solution to form a mixed solution with a PEI concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyampholyte CNT / PVA hydrogel was obtained by liquid nitrogen freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 h. The sample was frozen in a refrigerator and then dried in a freeze dryer for 48 h to obtain the CNT / PVA composite aerogel regulated by polyampholyte. The polyampholyte CNT / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the CNT / PVA hydrogel under the condition of light power density of 1 kW m -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 1.

[0081] Comparative Example 1

[0082] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyanionic CNT / PVA hydrogel was obtained by traditional freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 hours. The sample was frozen in a refrigerator and dried in a freeze dryer for 48 hours to obtain a polyanion-regulated CNT / PVA composite aerogel. The polyanion CNT / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The effect of the optical power density on the aerogel was also studied. -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 1.

[0083] Comparative Example 2

[0084] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / g / mL was prepared, and 5 mg / g / mL carbon nanotube slurry (CNT) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5. The cells were broken and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. No polyelectrolyte was added. After adjusting the pH of the mixed solution to about 1, it was vacuum degassed and a crosslinking agent glutaraldehyde solution was added to the mixed solution at a mass ratio of 1:100. The frozen CNT / PVA hydrogel was obtained by directional freeze casting with liquid nitrogen. The frozen composite gel was thawed at room temperature and placed in pure water for 24 hours. The sample after standing was frozen in a refrigerator and dried by a freeze dryer for 48 hours to obtain a CNT / PVA composite aerogel. After being placed in water for expansion, a CNT / PVA hydrogel was obtained. The average oriented pore size was further studied and counted, and its light power density was studied at 1 kW m -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 1.

[0085] Table 1 Test results of photothermal temperature and photothermal water evaporation rate of nanocarbon hydrogels obtained in Examples 1-3 and Comparative Examples 1-2

[0086]

[0087] Example 4

[0088] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL of graphene oxide slurry (GO) and 50 mg / mL of polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a GO / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyanionic GO / PVA hydrogel was obtained by liquid nitrogen freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 h. The sample was frozen in a refrigerator and then dried in a freeze dryer for 48 h to obtain the polyanion-regulated GO / PVA composite aerogel. The polyanion GO / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the GO / PVA hydrogel has a good optical power density of 1 kW m -2 The water evaporation rate under simulated sunlight is shown in Table 2.

[0089] Example 5

[0090] A polyvinyl alcohol (PVA) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon black slurry (CB) and 50 mg / mL polyvinyl alcohol (PVA) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CB / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyanionic CB / PVA hydrogel was obtained by liquid nitrogen freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 h. The sample was frozen in a refrigerator and then dried in a freeze dryer for 48 h to obtain the polyanion-regulated CB / PVA composite aerogel. The polyanion CB / PVA hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the composite aerogel had a good optical power density of 1 kW m -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 2.

[0091] Example 6

[0092] A polyethylene glycol (PEG) solution with a concentration of 50 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL polyethylene glycol (PEG) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PEG mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyanionic CNT / PEG hydrogel was obtained by liquid nitrogen freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 hours. The sample was frozen in a refrigerator and dried in a freeze dryer for 48 hours to obtain a polyanion-regulated CNT / PEG composite aerogel. The polyanion CNT / PEG hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the hydrogel had a good optical power density of 1 kWm -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 2.

[0093] Example 7

[0094] A polyethylene glycol (PEG) solution with a concentration of 20 mg / mL was prepared, and 5 mg / mL carbon nanotube slurry (CNT) and 20 mg / mL polyethylene glycol (PEG) solution were mixed and stirred at a volume ratio of 1:5, and the cells were broken and dispersed evenly for 5 hours to form a CNT / PEG mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was dropped into the above mixed solution to form a mixed solution with a PSSA concentration of 20 mg / mL. After adjusting the pH of the mixed solution to about 1, it was subjected to vacuum degassing treatment, and the crosslinking agent glutaraldehyde solution was added to the above mixed solution at a mass ratio of 1:100, and the frozen polyanionic CNT / PEG hydrogel was obtained by liquid nitrogen freeze casting. The frozen composite gel was thawed at room temperature and placed in pure water for 24 hours. The sample was frozen in a refrigerator and dried in a freeze dryer for 48 hours to obtain a polyanion-regulated CNT / PEG composite aerogel. The polyanion CNT / PEG hydrogel was obtained after being soaked in water. The average oriented pore size was further studied and counted. The results also showed that the hydrogel had a good optical power density of 1 kWm -2 The evaporation rate of solar hot water under simulated sunlight is shown in Table 2.

[0095] Table 2 Test results of photothermal temperature and photothermal water evaporation rate of nanocarbon hydrogels obtained in Examples 4-7

[0096]

[0097] Furthermore, infrared thermal imaging was used to observe the photothermal conversion state of the polyelectrolyte carbon-based hydrogel under a sunlight power density. Figure 3 It shows that polyelectrolyte carbon-based hydrogel has very excellent photothermal conversion properties.

[0098] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0099] The various aspects, embodiments, features and examples of the present invention should be considered to be illustrative in all aspects and are not intended to limit the present invention. The scope of the present invention is defined solely by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0100] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A polyelectrolyte carbon-based hydrogel, characterized in that: The polyelectrolyte carbon-based hydrogel has an ordered oriented three-dimensional porous network structure formed by cross-linking of water-soluble gel, polyelectrolyte and nano-carbon.

2. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that: The oriented pore size of the polyelectrolyte carbon-based hydrogel is 1 to 20 μm, preferably 1 to 10 μm; and / or, the porosity of the polyelectrolyte carbon-based hydrogel is 80-90%; And / or, the polyelectrolyte carbon-based hydrogel is -2 Under the light power density, the water evaporation rate is 1.8~4.3kgm -2 h -1 .

3. A method for preparing a polyelectrolyte carbon-based hydrogel, characterized in that: include: Evenly mixing the water-soluble gel, water and the nano-carbon material to obtain a first mixed solution; Mixing the polyelectrolyte and the first mixed solution uniformly to obtain a second mixed solution, and adjusting the pH value; The second mixed solution and the cross-linking agent are mixed and subjected to directional freeze casting to obtain a frozen nanocomposite gel; The frozen nano-carbon composite gel is freeze-dried to obtain a polyelectrolyte carbon-based aerogel, and then is soaked in water to obtain a polyelectrolyte carbon-based hydrogel.

4. The preparation method according to claim 3, characterized in that: include: Mixing the water-soluble gel with water to obtain a polymer solution, and adding nano-carbon material to obtain the first mixed solution; Preferably, the mass concentration of the water-soluble gel in the polymer solution is 10 to 50 mg / mL; Preferably, the mass concentration of the nanocarbon material in the first mixed solution is 0.1 to 2 mg / mL; Preferably, the water-soluble gel comprises at least any one of chitosan, sodium alginate, polyvinyl alcohol, and polyethylene glycol; Preferably, the nano-carbon material includes at least any one of graphene, carbon nanotubes, graphyne, fullerene, nano-carbon black, activated carbon, and graphite powder.

5. The preparation method according to claim 3, characterized in that: include: The polyelectrolyte and the first mixed solution are stirred and mixed uniformly to obtain a second mixed solution, and the pH value is adjusted to 1-2, and after stirring uniformly, vacuum degassing treatment is performed; Preferably, the polyelectrolyte comprises at least any one of a polyanion electrolyte, a polycation electrolyte, and a polyzwitterion electrolyte; Preferably, the polyanion electrolyte includes at least any one of polyacrylic acid, polyacrylamide, polymethacrylic acid, polystyrene sulfonic acid, and polyvinyl phosphoric acid; Preferably, the polycation electrolyte includes at least any one of polyethyleneimine and polyethyleneamine; Preferably, the amphoteric polyelectrolyte comprises at least any one of natural nucleic acid, protein, and polydimethyldiallylammonium chloride-acrylamide-acrylic acid; Preferably, the mass concentration of the polyelectrolyte in the second mixed solution is 10 to 50 mg / mL; Preferably, the acid used to adjust the pH includes at least one of hydrochloric acid, sulfuric acid, and phosphoric acid; Preferably, the concentration of the acid is 0.1 to 1 mol / L; Preferably, the vacuum degassing treatment time is 20 to 60 minutes, the vacuum degree of the vacuum degassing treatment is 1 to 20 Pa, and the temperature of the vacuum degassing treatment is 15 to 30°C.

6. The preparation method according to claim 3, characterized in that: include: The cross-linking agent is added dropwise to the second mixed solution, poured into a freeze casting mold, and subjected to directional freeze casting to obtain a frozen nano-carbon composite gel; Preferably, the mass ratio of the cross-linking agent to the second mixed solution is 1:100N1:200; Preferably, the cross-linking agent comprises glutaraldehyde; Preferably, the temperature of the directional freeze casting is -20 to -196°C; Preferably, the directional freezing casting includes unidirectional freezing or bidirectional freezing; Preferably, the working environment of the directional freeze casting is a low-temperature constant-temperature reaction bath or liquid nitrogen; Preferably, the raw material of the freeze casting mold includes at least any one of stainless steel, copper, aluminum, silicone, polytetrafluoroethylene, nylon, and plexiglass.

7. The preparation method according to claim 3, characterized in that: include: The frozen nano-carbon composite gel is thawed and allowed to stand at room temperature, and then freeze-dried to obtain a polyelectrolyte carbon-based aerogel, and then soaked in water to obtain a polyelectrolyte carbon-based hydrogel; Preferably, the standing time is 1 to 3 hours; Preferably, the freeze-drying time is 24 to 72 hours, and the freeze-drying temperature is 10 to 30°C; Preferably, the vacuum degree of freeze drying is 1 to 10 Pa; Preferably, the foaming time is 1 to 10 hours.

8. The polyelectrolyte carbon-based hydrogel prepared by the preparation method according to any one of claims 3 to 7.

9. A polyelectrolyte carbon-based xerogel prepared by drying the polyelectrolyte carbon-based hydrogel according to claim 8.

10. Use of the polyelectrolyte carbon-based hydrogel according to claim 8 or the polyelectrolyte carbon-based xerogel according to claim 9 in the field of photothermal water evaporation purification, preferably, the application includes use in seawater desalination, sewage treatment or heavy metal salt treatment.

Citation Information

Patent Citations

  • Preparation method and application of hydrogel film with porous structure

    CN118047973A

  • Efficient photo-thermal water evaporation carbon nanotube hydrogel as well as preparation method and application thereof

    CN112934129A

  • Hydrogel for solar water treatment as well as preparation method and application of hydrogel

    CN117089088A

  • Modified hydrogel for realizing high solar water evaporation rate as well as preparation method and application of modified hydrogel

    CN118236928A

  • Apparatus and method for transmitting power wirelessly

    KR1020240018857A

Cited By

  • Self-floating type double-layer solar evaporator with Janus characteristic and preparation method and application of self-floating type double-layer solar evaporator

    CN121159932A

  • Self-floating double-layer solar evaporator with Janus characteristics and preparation method and application thereof

    CN121159932B

  • Graphene composite hydrogel interface evaporation material as well as preparation method and application thereof

    CN121628265A